2009
DOI: 10.1177/0164027509348143
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of AIDS on Intergenerational Support in South Africa: Evidence From the Cape Area Panel Study

Abstract: This study uses panel data from Cape Town to document the role played by aging parents in caring for grandchildren who lose parents due to illnesses such as AIDS. We quantify the probabilities that older adults and their adult children provide financial support to orphaned grandchildren. We find significant transfers of public and private funds to older adults caring for orphans. Perhaps because of these transfers we find no differences in expenditure patterns between households with orphans and other older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…In previous related work using data from the Cape Area Panel Study (Ardington et al 2010), we document that significant public and private transfers are reported by older adults caring for orphaned children. Perhaps as a result of these transfers, we found no difference in expenditure patterns between older-adult households caring for orphans and other older adult households, and no significant difference in the wellbeing reported by older adults caring for orphans and other older adults.…”
mentioning
confidence: 64%
“…In previous related work using data from the Cape Area Panel Study (Ardington et al 2010), we document that significant public and private transfers are reported by older adults caring for orphaned children. Perhaps as a result of these transfers, we found no difference in expenditure patterns between older-adult households caring for orphans and other older adult households, and no significant difference in the wellbeing reported by older adults caring for orphans and other older adults.…”
mentioning
confidence: 64%
“…These include unconditional and conditional cash transfer programmes, as well as government-funded social grants, intended for caregivers of orphans and vulnerable children (OVC) (Ardington et al, 2010; Miller & Tsoka, 2012; Niño-Zarazúa et al, 2012; Robertson et al, 2013; Twine, Collinson, Polzer, & Kahn, 2007). A number of these programmes have shown improved nutritional and educational outcomes for OVCs in homes that receive cash assistance (Adato & Bassett, 2009; Ayuku et al, 2014; Wakoli, Ettyang, & Lakati, 2012).…”
Section: The Care Deficitmentioning
confidence: 99%
“…For example, old-age pension spending in South Africa directly helps child outcomes. The introduction of a large-scale pension provision to women over 60 and men over 65 has resulted in a number of well-documented child health outcomes such as improved schooling and nutrition (Case & Menendez, 2007), and contributes to a financial buffer that protects both outcomes for orphan children and the elderly from assaults such as parental AIDS deaths (Ardington et al, 2010). Such investment initiatives provide a multigenerational investment.…”
Section: Gaps In Knowledge and Questions For Further Discussionmentioning
confidence: 99%